The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1007/s11244-017-0836-7
|View full text |Cite
|
Sign up to set email alerts
|

Operando Spectroscopy of the Gas-Phase Aldol Condensation of Propanal over Solid Base Catalysts

Abstract: time. In particular, for Cs-X and Ca-HA the rapid formation of carbonaceous deposits was observed consisting of (poly-)aromatics and highly conjugated structures, respectively. The physicochemical properties of Ca-HA with strong basic sites and moderate acidity limit its deactivation despite the observed coke formation. On the other hand, both USY catalysts were more efficient in suppressing coke formation likely due to the moderate strength of their active sites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 57 publications
1
33
0
Order By: Relevance
“…Mini review Hinshelwood type reaction, although Eley-Rideal mechanisms were proposed for the condensation of other short-chain aldehydes. 132,133 While the formation of crotonaldehyde via the aldol condensation of acetaldehyde is generally accepted as a keystep of the Toussaint-Kagan pathway from ethanol to butadiene, our understanding of the molecular-level phenomena taking place remains limited. Several mechanisms have been proposed, but the direct observation of surface intermediates and their correlation to activity has been limited, ostensibly due to their high instability.…”
Section: Catalysis Science and Technologymentioning
confidence: 99%
“…Mini review Hinshelwood type reaction, although Eley-Rideal mechanisms were proposed for the condensation of other short-chain aldehydes. 132,133 While the formation of crotonaldehyde via the aldol condensation of acetaldehyde is generally accepted as a keystep of the Toussaint-Kagan pathway from ethanol to butadiene, our understanding of the molecular-level phenomena taking place remains limited. Several mechanisms have been proposed, but the direct observation of surface intermediates and their correlation to activity has been limited, ostensibly due to their high instability.…”
Section: Catalysis Science and Technologymentioning
confidence: 99%
“…Mechanistic studies of aldehyde dimerization over HAP at 533-673 K by Young et al and Hernández-Giménez et al have suggested that product desorption is slow in the absence of a hydrogen donor [57,58]. If product desorption is rate-limiting, then every surface reaction prior to that step is quasi-equilibrated, including the dehydration of DAA.…”
Section: Acetone Condensation Over Ie-hapmentioning
confidence: 99%
“…Increasing temperature, only gas-phase species were observed, detected in the cooled-down spectra. Thus, IR bands at 1722 and 1700 cm -1 appeared at 160°C and 240°C, corresponding to PAL [34 ] and acetone [35 ] respectively. These species derived from the acid catalyzed 1,2-PD dehydration path, being easily desorbed to the gas phase.…”
Section: Ftir Spectra Of Adsorbed 12-pdmentioning
confidence: 97%